A Complete Study of Digital Payment System in India - Dr. Rekha Kumawat (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
This research paper presents an in-depth study of the Unified Payments Interface (UPI) ecosystem in India, focusing on its application dynamics and market leadership. Conducted in the Pune region, the study gathered primary data through a questionnaire survey of 82 respondents, complemented by extensive secondary data analysis to provide a comprehensive understanding of the industry.UPI, launched in 2016 by the National Payments Corporation of India (NPCI), is a real-time payment system enabling seamless Peer-to-Peer (P2P) and Person-to-Merchant (P2M) transactions across multiple bank accounts via a single application. Its ease of use, security features, and instant transaction alerts have driven its widespread adoption, making it the cornerstone of India’s digital payment landscape.This paper specifically examines five major UPI applications-Google Pay, PhonePe, Amazon Pay, Paytm, and BHIM-analyzing their market share, transaction volumes, and user preferences. The study highlights the rapid growth of UPI, which accounted for over 131 billion transactions worth nearly ₹200 lakh crore in FY 2023-24, with continued expansion into international markets.PhonePe leads the market with approximately 47.5% share by transaction volume, followed by Google Pay and Paytm, reflecting competitive dynamics within the sector.The findings underscore UPI’s pivotal role in India’s digitalization journey, driven by smartphone proliferation and government initiatives, and project sustained growth as the platform continues to evolve and expand its user base both domestically and globally.
Keywords: Unified Payments Interface; Digital Payments; Market Share Analysis; Fintech Applications